Activated Clotting Time Requires Adaptation Across Altered Measurement Devices: Determination of Appropriate Range During Atrial Fibrillation Ablation - Haruna Sakanoue RN; Hirosuke Yamaji MD; Sayaka Okamoto RN; Kumi Okano RN; Yuka Fujita RN; Shunichi Higashiya MD; Takashi Murakami MD; Satoshi Hirohata MD; Shozo Kusachi MD (Clinical and Applied Thrombosis/Hemostasis)
Background Methods for measuring activated clotting time (ACT) are not yet standardized. Objectives To adjust and compare values between two measurement systems and to optimize ACT during atrial fibrillation (AF) ablation. Methods Two systems were compared: electromagnetic detection using a rotating tube (EM system; Hemochron Response) and photo-optical detection using a cartridge immersed in blood (PO system; ACT CA-300TM). Results ACT was measured simultaneously in 124 instances in 53 patients before and during AF ablations using both methods. A linear regression analysis showed ACT (EM system) = 1.19 × ACT (PO system) + 9.03 (p < .001, r = 0.90). Bland–Altman plots indicated an average difference of 50 s between the two systems. In 3364 ACT measurements from 1161 ablations, the EM system recorded a mean ACT of 320 ± 44 s (range 156-487 s). Estimating the target range as mean ± 1 SD range, the EM system's range was 275-365 s, in 5-s increments. The pre-ablation ACT measured on the EM system was 143 ± 28 s (115-170 s). Cardiac tamponade occurred in 4 out of 2085 ablations (0.19%) over 5 years, with ACT values ranging from 330 to 391 s on the EM system. Based on these findings, the estimated optimal ACT range for the PO system was adjusted to 225-300 s to align with the EM system's range of 275-365 s. Conclusions ACT target ranges should be system-specific, and direct extrapolation between devices is not recommended. Adjustment is clinically necessary when switching systems.